Submission by the Food and Agriculture Organization of the United Nations (FAO) and CGIAR to the United Nations Framework Convention on Climate Change (UNFCCC) in relation to the topic of the second dialogue under the United Arab Emirates Just Transition Work Programme - Food and Agriculture Organization of the United Nations; CGIAR (2024)
Food and Agriculture Organization of the United Nations (FAO) and the Consultative Group on International Agricultural Research (CGIAR) welcome the opportunity to submit views on opportunities, best practices, actionable solutions, challenges and barriers relevant to the topic of the second dialogue on “Ensuring support for people-centric and equitable just transition pathways with a focus on the whole of-society approach and the workforce”, under the United Arab Emirates Just Transition Work Programme (UAE JTWP) in relation to decision 3/CMA.5, para. 3-4.Agriculture is highly vulnerable to and severely impacted by climate change, at the same time as being a major contributor to greenhouse gas emissions, deforestation, and water use globally. Today, 1.23 billion people are employed in agrifood systems, while 3.83 billion people worldwide live in households linked to agrifood systems-based livelihoods1